2013
DOI: 10.1007/s12094-013-1136-8
|View full text |Cite
|
Sign up to set email alerts
|

CHD1L is a novel independent prognostic factor for gastric cancer

Abstract: These results indicated that CHD1L could serve as a prognostic marker for GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Moreover, the frequency of CHDIL overexpression increased with an ascending pN status and advancing clinical stage in NSCLC, especially in lung ADCs. Similar results were also observed in other types of human cancer [ 6 , 8 , 9 ]. In HCC, overexpression of CHD1L was associated closely with microsatellite formation and venous invasion [ 6 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover, the frequency of CHDIL overexpression increased with an ascending pN status and advancing clinical stage in NSCLC, especially in lung ADCs. Similar results were also observed in other types of human cancer [ 6 , 8 , 9 ]. In HCC, overexpression of CHD1L was associated closely with microsatellite formation and venous invasion [ 6 ].…”
Section: Discussionsupporting
confidence: 88%
“…In HCC, overexpression of CHD1L was associated closely with microsatellite formation and venous invasion [ 6 ]. In gastric cancer, up-regulated expression of CHD1L was reported to be correlated with tumor depth, nodal involvement and distant metastasis [ 9 ]. While in breast cancer, presence of CHD1L expression was associated with higher Ki-67 index and HER2 amplification [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chromodomain helicase/ATPase DNA binding protein 1-like gene (CHD1L gene) was originally isolated from hepatocellular carcinoma tissue and identified as an oncogene in our previous study (9). A functional study using CHD1L transgenic mice has confirmed its role in tumorigenesis (10), and epidemiological studies have suggested that CHD1L is either associated with cancer-inducing processes or can be used as a predictive biomarker for hepatocellular carcinoma (11)(12)(13) and several other cancers, such as ovarian carcinoma (14), bladder cancer (15), colorectal carcinoma (16), breast cancer (17), lung adenocarcinoma (18), glioma (19), and gastric cancer (20). CHD1L has also been defined as an ATP-dependent chromatin-remodeling enzyme that plays an important role in preserving chromosome integrity and promoting DNA repair (21).…”
mentioning
confidence: 53%